The Potency Of Extract Tegining Ganang Leaf (Cassia Planisiqua Burm.f.) As Analgesic On Mice (Mus musculus L.) By Chemical And Hot Plate Induction Method - Sister Sianturi; Amelia Febriani; Rahmi Syariifatul; Desy Satrana (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Tegining ganang (Cassia planisiliqua) is an indigenous plant of Lombok, West Nusa Tenggara which has potentials to treat various diseases. Previous research showed that the plant has analgesic activity, but the results were still less satisfactory due to the low analgesic effectiveness (<50 %). This study aimed to examine the analgesic potential of tegining ganang leaf extract through chemical induction and hot plate induction methods. In vivo testing was conducted on male mice using those two methods to evaluate plant effectiveness as both a central and peripheral analgesic. Tegining ganang leaves collected from the village of Peresak, West Lombok, West Nusa Tenggara Province, were extracted in ethanol 70%. The treatments were extract dosages, viz. 200, 400, 800 mg.kg-1 body weight (BW) of mice. The positive control treatments for the chemical induction and hot plate induction methods were Acetosal and Tramadol, respectively. Meanwhile, the negative control treatment was Na CMC at 0.5%. The analgesic effectiveness of the extract in both chemical and hot plate induction methods was 50 %. The optimum effectiveness for chemical induction was at 800 mg.kg-1 body weight, whereas for hot plate induction was at 200 mg.kg-1 body weight. The results indicated that the ethanol extract of tegining ganang leaves was potential to be developed as an analgesic material.